Potential anti-acanthamoebic effects through inhibition of CYP51 by novel quinazolinones - Usman, Ahmed *; Ho, Keat Yie; Simon, Samson Eugin *; Saad, Syed Muhammad; Ong, Seng Kai *; Areeba, Anwar; Tan, Kuan Onn *; Nanthini, Sridewi; Khan, Khalid Mohammed; Khan, Naveed Ahmed; Ayaz, Anwar * (Elsevier, 2022)
Acanthamoeba spp. are free living amoebae which can give rise to Acanthamoeba keratitis and granulomatous amoebic encephalitis. The surface of Acanthamoeba contains ergosterol which is an important target for drug development against eukaryotic microorganisms. A library of ten functionally diverse quinazolinone derivatives (Q1–Q10) were synthesised to assess their activity against Acanthamoeba castellanii T4. The in-vitro effectiveness of these quinazolinones were investigated against Acanthamoeba castellanii by amoebicidal, excystation, host cell cytopathogenicity, and NADPH-cytochrome c reductase assays. Furthermore, wound healing capability was assessed at different time durations. Maximum inhibition at 50 μg/mL was recorded for compounds Q5, Q6 and Q8, while the compound Q3 did not exhibit amoebicidal effects at tested concentrations. Moreover, LDH assay was conducted to assess the cytotoxicity of quinazolinones against HaCaT cell line. The results of wound healing assay revealed that all compounds are not cytotoxic and are likely to promote wound healing at 10 μg/mL. The excystation assays revealed that these compounds significantly inhibit the morphological transformation of A. castellanii. Compound Q3, Q7 and Q8 elevated the level of NADPH-cytochrome c reductase up to five folds. Sterol 14alpha-demethylase (CYP51) a reference enzyme in ergosterol pathway was used as a potential target for anti-amoebic drugs. In this study using i-Tasser, the protein structure of Acanthamoeba castellanii (AcCYP51) was developed in comparison with Naegleria fowleri protein (NfCYP51) structure. The sequence alignment of both proteins has shown 42.72% identity. Compounds Q1-Q10 were then molecularly docked with the predicted AcCYP51. Out of ten quinazolinones, three compounds (Q3, Q7 and Q8) showed good binding activity within 3 Å of TYR 114. The in-silico study confirmed that these compounds are the inhibitor of CYP51 target site. This report presents several potential lead compounds belonging to quinazolinone derivatives for drug discovery against Acanthamoeba infections.